2013
DOI: 10.1111/jgh.12125
|View full text |Cite
|
Sign up to set email alerts
|

Gastroesophageal Reflux Disease Questionnaire (GerdQ) in real‐world practice: A national multicenter survey on 8065 patients

Abstract: The study suggests the proportions of Chinese patients with reflux esophagitis rise up with the increase of GerdQ score, and GerdQ may be used for diagnosis of GERD. However, low GerdQ score cannot exclude the possibility of reflux esophagitis. A minority of Chinese patients has high GerdQ score but is diagnosed with malignancies, even in the absence of alarm features.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
58
0
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(69 citation statements)
references
References 19 publications
5
58
0
6
Order By: Relevance
“…These findings suggest that though GERD-Q may be used to diagnose GERD, endoscopy is still needed for some patients in populations with a high prevalence of upper gastrointestinal malignancies, like the Chinese. 24 Based on this finding and on our results, we think that further studies should be performed in the Spanish population to assess the exact correlation between GERD-Q score and the presence of esophagitis, in order to validate the questionnaire as a diagnostic tool for use in routine clinical practice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings suggest that though GERD-Q may be used to diagnose GERD, endoscopy is still needed for some patients in populations with a high prevalence of upper gastrointestinal malignancies, like the Chinese. 24 Based on this finding and on our results, we think that further studies should be performed in the Spanish population to assess the exact correlation between GERD-Q score and the presence of esophagitis, in order to validate the questionnaire as a diagnostic tool for use in routine clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…2,13,14,24,28 A recent study assessing the value of the GERD-Q found an association between higher GERD-Q scores and higher proportions of patients with reflux esophagitis. 24 However, the same study found that a low score could not rule out the possibility of reflux esophagitis, and also that a high score cannot exclude the possibility of upper gastrointestinal malignancies. These findings suggest that though GERD-Q may be used to diagnose GERD, endoscopy is still needed for some patients in populations with a high prevalence of upper gastrointestinal malignancies, like the Chinese.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Eastern Asia, the lifestyle and dietary habits have changed towards a more Western style, and the prevalence of GERD is likely to have increased as a result. [4][5][6][7][8][9] However, limited data exist on the response to PPI therapy and the recurrence of GERD in East Asian countries, including Korea. [10][11][12][13] Patients with GERD have a decreased health-related quality of life (HRQoL).…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9] Obesity may be the important cause of discrepancy in the prevalence of GERD between Eastern and Western countries. 30 Obesity was associated with frequent GERD symptoms in a dosedependent manner.…”
mentioning
confidence: 99%